Use of unit root methods in early warning of financial crises - Timo Virtanen; Eero Tölö; Matti Virén; Katja Taipalus (European Systemic Risk Board, 2025)
In several recent studies unit root methods have been used in detection of financial bubbles in asset prices. The basic idea is that fundamental changes in the autocorrelation structure of rel-evant time series imply the presence of a rational price bubble. We provide cross-country evi-dence for performance of unit-root-based early warning systems in ex-ante prediction of finan-cial crises in 15 EU countries over the past three decades. We find especially high performance for time series that are explicitly related to debt, which issue signals a few years in advance of a crisis. Combining signals from multiple time series further improves the predictions. Our results suggest an early warning tool based on unit root methods provides a valuable accessory in financial stability supervision.